Efficacy of early sivelestat administration on acute lung injury and acute respiratory distress syndrome. Issue 4 (18th December 2016) - Kido, Takashi; Muramatsu, Keiji; Yatera, Kazuhiro; Asakawa, Takeshi; Otsubo, Hiroki; Kubo, Tatsuhiko; Fujino, Yoshihisa; Matsuda, Shinya; Mayumi, Toshihiko; Mukae, Hiroshi
ABSTRACT: Background and objective: The efficacy of sivelestat, a neutrophil elastase inhibitor, for acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) remains controversial. We investigated the role of sivelestat in ALI/ARDS patients on mortality as an end point between the sivelestat group and the non‐sivelestat group within 7 days of admission. Methods: This study was performed using the Japanese nationwide administrative database (Diagnostic Procedure Combination; DPC) in 2012. We employed the propensity score weighting method with a Cox proportional hazards model to compare the mortality between the sivelestat group and the non‐sivelestat group. Results: A total of 4276 patients were eligible for this study; 1997 patients were treated with sivelestat and 2279 patients did not receive sivelestat within 7 days of admission. After adjusting for confounds, the mortality within 3 months was significantly lower in the sivelestat group compared with the non‐sivelestat group (weighted hazard ratio: 0.83; 95% CI: 0.75–0.93; P  < 0.002). Multiple regression analysis revealed that younger age, absence of cancer, no need for haemodialysis and no use of high‐dose methylprednisolone were significantly correlated with treatment success (survive). Conclusion: These results of this retrospective and observational study suggest that administration of sivelestat within 7 days of admission may improve the prognosis of patients with ALI/ARDS. To our knowledge, this is the largest study to evaluate the efficacy of sivelestat on ALI/ARDS. Abstract : Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are critical respiratory diseases. No effective pharmacotherapies have been established and the efficacy of sivelestat for ALI/ARDS remains uncertain. Our results suggest that early sivelestat administration may improve the prognosis of patients with ALI/ARDS.